A dual role for integrin-linked kinase in platelets: regulating integrin function and alpha-granule secretion. - Tucker, K; Sage, T; Stevens, J; Jordan, P; Jones, S; Barrett, N; St-Arnaud, R; Frampton, J; Dedhar, S; Gibbins, J (2008)
Integrin-linked kinase (ILK) has been implicated in the regulation of a range of fundamental biological processes such as cell survival, growth, differentiation, and adhesion. In platelets ILK associates with beta1- and beta3-containing integrins, which are of paramount importance for the function of platelets. Upon stimulation of platelets this association with the integrins is increased and ILK kinase activity is up-regulated, suggesting that ILK may be important for the coordination of platelet responses. In this study a conditional knockout mouse model was developed to examine the role of ILK in platelets. The ILK-deficient mice showed an increased bleeding time and volume, and despite normal ultrastructure the function of ILK-deficient platelets was decreased significantly. This included reduced aggregation, fibrinogen binding, and thrombus formation under arterial flow conditions. Furthermore, although early collagen stimulated signaling such as PLCgamma2 phosphorylation and calcium mobilization were unaffected in ILK-deficient platelets, a selective defect in alpha-granule, but not dense-granule, secretion was observed. These results indicate that as well as involvement in the control of integrin affinity, ILK is required for alpha-granule secretion and therefore may play a central role in the regulation of platelet function.